Nuclear dependence of light neutral meson production in p–A collisions at 400 GeV with NA60 - R. Arnaldi; K. Banicz; K. Borer; J. Castor; B. Chaurand; W. Chen; C. Cicalò; A. Colla; P. Cortese; S. Damjanovic; A. David; A. De Falco; et al. (European Physical Journal C: Particles and Fields, 2019)
Abstract The NA60 experiment has studied low-mass muon pair production in proton–nucleus collisions with a system of Be, Cu, In, W, Pb and U targets, using a 400 GeV proton beam at the CERN SPS. The transverse momentum spectra of the $$\rho /\omega $$ ρ/ω and $$\phi $$ ϕ mesons are measured in the full $$p_{\mathrm {T}}$$ pT range accessible, from $$p_{\mathrm {T}}= 0$$ pT=0 up to $$2 \, {\hbox {GeV/c}}$$ 2GeV/c . The nuclear dependence of the production cross sections of the $$\eta $$ η , $$\omega $$ ω and $$\phi $$ ϕ mesons has been found to be consistent with the power law $$\sigma _{\mathrm {pA}} \propto {\mathrm {A}}^\alpha $$ σpA∝Aα , with the $$\alpha $$ α parameter increasing as a function of $$p_{\mathrm {T}}$$ pT for all the particles, and an approximate hierarchy $$\alpha _\eta \approx \alpha _\phi > \alpha _\omega $$ αη≈αϕ>αω . The cross section ratios $$\sigma _\eta /\sigma _\omega $$ ση/σω , $$\sigma _\rho /\sigma _\omega $$ σρ/σω and $$\sigma _\phi /\sigma _\omega $$ σϕ/σω have been studied as a function of the size A of the production target, and an increase of the $$\eta $$ η and $$\phi $$ ϕ yields relative to the $$\omega $$ ω is observed from p–Be to p–U collisions.